HIGHER EDUCATION DEVELOPMENT STRATEGY USING INTERNAL RESOURCES AND MARKETING MIX STRATEGY: HIGHER EDUCATION DEVELOPMENT STRATEGY USING INTERNAL RESOURCES AND MARKETING MIX STRATEGY - Heru Yulianto; Bambang Widjanarko Susilo (Brilliant International Journal Of Management And Tourism, 2022)
ABSTRACT As a producer of educational services, higher education is still a seller's market and potential students are flocking to enroll in higher education. The number of PTS and the number of students are relatively large, which causes competition between PTS, with the aim that future students choose higher education more rationally based on their own understanding of changes in the environment. For private higher education providers, the customers who directly use their services are students, and the competitors are providers of educational services at the same level. Changes include academic and non-academic internal initiatives and various forms of external pressure for this satisfactory agency service created by the marketing mix. Elements of this marketing mix strategy include 7P, 4P marketing mix (product, price, channel, advertising) and internal 3P resources (people, process, physical evidence) in service marketing